Correlation of nailfold capillaroscopic changes using handheld dermatoscope with varying grades and severity of diabetic retinopathy in patients with type 2 diabetes mellitus: A pilot observational cross-sectional analytical study - Rohit Raina; Neha Chhabra; Shruti Barnwal; Shivani Vasisht; Naveen Kumar Kansal; Ravi Kant (Journal of Clinical Ophthalmology and Research)
Background: Diabetic retinopathy (DR) is a microvascular disorder occurring due to the long-term effects of diabetes mellitus (DM). Nailfold capillaroscopy (NFC) is an in vivo study of microvascular circulation to predict the grade and severity of DR. Aim: The present study is a cross-sectional observational study that attempts to describe and quantify the NFC changes using handheld dermatoscope in type 2 DM patients with retinopathy changes and to assess whether it has any correlation with varying grades and severity of DR. Materials and Methods: A cross-sectional observational study was conducted in AIIMS, Rishikesh, over a period of 6 months from August 2022 to February 2023. Our study participants were 54 Type 2 diabetic patients more than 18 years of age diagnosed with DR using standard Early Treatment DR Study. For all the study participants, a detailed NFC was done for all 8 fingernails (excluding the thumb), using a handheld dermatoscope. Abnormal capillary shapes were recorded by semiquantitative score (NFC score). The data normality was checked using Kolmogorov–Smirnov test. Results: Significant association was seen in the total number of avascular areas/3 mm, abrogated/bushy capillaries/3 mm, number of fingers involved excluding thumb, and total nailfold capillaroscopic score with varying grade of DR (P < 0.05). Patients with avascular areas/3 mm, tortuous capillaries/3 mm, and abrogated/bushy capillaries/3 mm were significantly higher (P < 0.05) in advanced diabetic eye disease and diabetic macular edema (DME). All patients with advanced diabetic eye disease and DME had any finger involved excluding the thumb with abnormal NFC score which indicates the highest correlation between the severity of retinopathy and involvement of microvascular abnormality in the proximal nailfold. Conclusion: Our results suggest that NFC could possibly be used as an adjunctive tool in diabetics for diagnosing or monitoring the grade and severity of DR. NFC features are predominantly proliferative in early stages (capillary dilation, giant or bushy capillaries) and regressive in long-standing disease (such as capillary dropouts and avascular areas).